Hubungan Kekerabatan Bahasa Jawa, Sunda, dan Makassar: Kajian Linguistik Historis Komparatif - Siti Sulistiyarini; Hendrokumoro Hendrokumoro (Balai Bahasa Provinsi Riau, 2023)
This study aims to explain the kinship of Javanese (JL), Sundanese (SL), and Makassar (ML) languages ​​seen from the percentage of kinship, time of separation, and correspondence of their sounds. Through quantitative and descriptive qualitative methods, this study examines two hundred Swadesh vocabularies obtained from JL, SL, and ML native speakers using lexicostatistics and glottochronology techniques. The results of this study indicate that JL, SL, and ML are related and come from the same protolanguage with a kinship percentage of JL – SL 43%, JL – ML 20%, and SL – ML 16%. The separation times of the three languages ​​are JL – SL between 185 BC – 231 AD, BL – ML between 2131 BC – 1463 BC, and SL – ML between 2737 BC – 1917 BC calculated in 2023. Found 19 pairs of identical words; 9 correspondence phonemes, and 2 phonetic similarities.